Enhancing Lubricating Oil Performance Through the Integration of Viscosity Improvers in Mono-Grade and Multi-Grade Blends - Nnadikwe Johnson; Iheme Chigozie; Samuel Nwaozuzu; Tare Caroline Gillow (Journal Majelis Paspama, 2026)
This study focuses on enhancing lubricating oil performance through the integration of viscosity improvers in multi-grade blends. A systematic approach was followed to formulate a high-performance multi-grade engine oil, starting with 5 liters of base oil and 1 liter of paraffin oil (100N). Additives (0.42 kg, 7% of the total blend) including Aspen, Tackifier, anti-wear, corrosion inhibitors, detergents, dispersants, and antioxidants were meticulously measured and added to the mix. The mixture was heated to 70°C to facilitate reaction between the base oil and additives, and then cooled to room temperature (around 30°C). Subsequently, 0.5 kg of viscosity index improver was introduced into the mixture, followed by the addition of 5 grams of dye. Quality control tests were conducted to ensure compliance with Standard Organization of Nigeria (SON) standards. The results showed that the product met the stringent specifications outlined by the regulatory body, demonstrating reliability and performance. This study highlights the importance of viscosity improvers in enhancing lubricating oil performance and meeting industry standards.